2005
DOI: 10.1074/jbc.m507338200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Application of Nicotinic Acid Adenine Dinucleotide Phosphate Induces Ca2+ Signaling in Astrocytes in Situ

Abstract: Astrocytes are in intimate contact with neurons, in particular with synapses, and are able to sense, react to, and even influence neuronal activity. The astrocytic response to neuronal activity can be most readily detected by observing changes in the intracellular Ca 2ϩ concentration mediated via transmitter receptors (e.g. glutamate, GABA (␥-aminobutyric acid), or acetylcholine) or via other messengers, such as nitric oxide. Ca 2ϩ increases can occur by Ca 2ϩ influx via the plasma membrane as found for the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 45 publications
(46 reference statements)
7
50
1
Order By: Relevance
“…Despite this biochemical data, functional evidence for NAADP signalling in mammalian neurons is scant. In addition to possible extracellular effects of NAADP [49], we have shown intracellular delivery of NAADP in to cortical neurons and PC12 cells mediates Ca 2+ signals that are inhibited by acid store blockers but readily demonstrable following depletion of endoplasmic reticulum Ca 2+ stores with thapsigargin [50;51]. We also confirmed the presence of NAADP receptors in the former preparation using a novel cell permeable acetoxymethyl ester of NAADP [52].…”
Section: +supporting
confidence: 58%
“…Despite this biochemical data, functional evidence for NAADP signalling in mammalian neurons is scant. In addition to possible extracellular effects of NAADP [49], we have shown intracellular delivery of NAADP in to cortical neurons and PC12 cells mediates Ca 2+ signals that are inhibited by acid store blockers but readily demonstrable following depletion of endoplasmic reticulum Ca 2+ stores with thapsigargin [50;51]. We also confirmed the presence of NAADP receptors in the former preparation using a novel cell permeable acetoxymethyl ester of NAADP [52].…”
Section: +supporting
confidence: 58%
“…This is consistent with the findings of Billington et al (24), showing that NAADP is efficiently transported in a Na ϩ -and Ca 2ϩ -dependent manner in RBL-2H3 cells, resulting in an elevation in intracellular Ca 2ϩ . That extracellular application of NAADP is effective in evoking Ca 2ϩ responses in glial and neuronal cells (21)(22)(23) has also been reported, although the response may have been mediated by the adenosine receptors or by purinergic receptors. The impermeability reported previously could be due to a non-conducive condition used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to targeting intracellular Ca 2ϩ stores, extracellular application of NAADP has also been reported to induce intracellular Ca 2ϩ changes, possibly via activation of surface adenosine receptors or purinergic receptors (21)(22)(23). That NAADP can be efficiently transported into cells has been shown in a rat basophilic cell line and a neuroblastoma cell line, resulting in elevation of intracellular Ca 2ϩ (24).…”
Section: Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp)mentioning
confidence: 99%
“…On the other hand, contractions were markedly attenuated by pharmacological inhibition of P2X receptors, suggesting that NADP(H) may also be able to act directly on purinergic receptors (26). Furthermore, 2 different reports have proposed a role of extracellular NAADP in the activation of purinergic receptors (27,28), although it has also been shown that NAADP and cADPR can be transported into cells (see below).…”
Section: And Elena Zocchimentioning
confidence: 97%
“…The predominantly extracellular or intravesicular location of CD38 raises the question of whether extracellularly produced cADPR and NAADP can cross the plasma membrane (29). Surprisingly, it has been shown that both extracellular cADPR and NAADP enter cells and raise intracellular Ca 2+ concentrations (9,27,30). The entry of cADPR into cells is mediated by CD38 itself as well as by members of both the equilibrative (ENT2) and the concentrative nucleoside transporter (CNT2, CNT3, and especially cs-csg) families, as determined by both pharmacology and molecular biology (9).…”
Section: Can Cd38-synthesized Messengers Reach Their Intracellular Tamentioning
confidence: 99%